Pengaruh Terpaan Iklan Bukalapak di Televisi dan Intensitas Komunikasi Word of Mouth Terhadap Minat Bertransaksi di Bukalapak - Septiani Cahyaning Tyas; Sri Widowati Herieningsih (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
This research aims to determine the effect of Bukalapak advertising exposure by analyzing the intensity of word of mouth communication on the interest in making transactions in Bukalapak. Theories used are Strong Theory of Communication and Buyer information environment theory.* The sampling technique used is nonprobability sampling, conducted by accidental sampling with a sample of 60 people with the criteria as follow; men and women aged 17-35 years who lived in Semarang, had watched Bukalapak advertisements on television, had discussed in person or online about Bukalapak and have never transacted in Bukalapak. Survey are carried out using the Simple Linear Regression Test. The results showed that the significance value for the Bukalapak advertising exposure variable on television and variable word of mouth communication intensity were 0,000, which means very significant. This shows that there is an influence of Bukalapak advertising on Television (X1) toward people interest in transacting in Bukalapak (Y) by 44.9%. Also, the influence between the intensity of word of mouth communication (X2) on the interest in transacting in Bukalapak by 58.5%.